Trends and challenges of community service participation among postgraduate students in IIUM: a case study - Mohamad Diah, Nurazzura; Nurul Farhanah, Mohd Nasir (Serial Publications, 2016)
University-community engagement is important for students’ knowledge enrichment because it exposes them to fieldwork. Experiences gained will help students to prepare themselves for future careers and expose them to a holistic view of the community expectations toward university graduates. This paper attempts to explain the trends and challenges of community service participation among postgraduate students of International Islamic University Malaysia (IIUM). Data was gathered using in-depth interview. Twenty postgraduate students, both local and international participated in this study. Data analysis was performed using qualitative approach. In general, this study reveals that postgraduate students believed that community service is the responsibility of undergraduate students due to the fact that their main focus is more on academic related work. Those who participated would have to juggle between their studies, work and family. Interestingly, socio-cultural barriers, particularly language barriers and cultural boundaries are amongst the problems that discourage international postgraduate students from participating in community service activities. Indeed, community service is an important agenda in any university to develop human capital. The university needs to strengthen its structural environment, thus making students from various socio-cultural backgrounds realize that they have a role to play in the community